Some results on weakly inward mapping in geodesic metric spaces - khalid alisawi; Salwa Salman Abed (Al-Qadisiyah Journal of Pure Science, 2020)
Geodesic spaces are convex nonlinear spaces. Convexity is a significant tool to generalize some properties of Banach spaces. In this paper, the characterization of weakly inward was extended to CAT(0) spaces and give equivalent condition for the existence of fixed point for multivalued mapping